Changes in Total Phenolic Content Due to Changes in Storage Temperature, Crown Pruning, and Pineapple Fruit Coating - Chandra, David; Widodo, Soesiladi Esti; Kamal, Muhammad; Waluyo, Sri; Zulferiyenni, Zulferiyenni; Yosilia, Rani (ORGANISMS: JOURNAL OF BIOSCIENCES, 2026)
Phenolic compounds are substrates for the internal browning (IB) reaction in pineapple fruit, and their accumulation increases at high temperatures. However, the effect of temperature changes after prolonged cold storage on total phenolic content (TPC) remains unclear. This study evaluated the effects of storage temperature, crown pruning, and fruit coating on TPC and its correlations with IB incidence and severity, and vitamin C. GP3 and MD2 pineapple clones were arranged in a three-factor randomized block design with storage temperature (7 and 7+16 °C), crown treatment (intact crown and crown pruning), and fruit coating (50 mg L-1 ABA, 1% chitosan, ABA + chitosan, and H2O). The results showed that changing the storage temperature to room temperature for 2 days and pruning the crown at day 30 increased TPC and fruit color darkness. The interaction of changes in storage temperature and crown pruning was the treatment that produced the highest TPC. The application of fruit coating had no significant effect on TPC. The incidence and severity of IB were not affected by TPC, but were negatively correlated to the vitamin C content in pineapple. It is concluded that the presence of high enough vitamin C can suppress IB, even though the TPC content is quite high in pineapple.